2022
DOI: 10.3390/nu14235046
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of Healthy Behaviour on the Association of Frailty with Respiratory Diseases Mortality among 0.4 Million Participants: A Prospective Cohort Study from UK Biobank

Abstract: The mutual relationship between frailty and healthy behaviour and its effect on respiratory diseases mortality remains largely unknown; this study aims to supplement related analysis on it by using a large sample cohort study. We included 411,987 participants from the UK Biobank study (2006–2021), and measured participants’ frailty phenotype and healthy behaviour index by using questionnaires and physical measurement. Mortality from respiratory diseases were obtained through linkage to registries. We used the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…We measured the interaction of the product term. 26,27 To further assess the robustness of results, we did the sensitivity analysis 1: we used continuous mode of these variables including age, mpox-related knowledge and sexual diseases scores in model 3. To compare the estimates of specific sexual behaviors, we supplemented the associations of three sexual behaviors including condomless anal intercourse, commercial sex, and group sex in the last month with mpox.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured the interaction of the product term. 26,27 To further assess the robustness of results, we did the sensitivity analysis 1: we used continuous mode of these variables including age, mpox-related knowledge and sexual diseases scores in model 3. To compare the estimates of specific sexual behaviors, we supplemented the associations of three sexual behaviors including condomless anal intercourse, commercial sex, and group sex in the last month with mpox.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of an interaction was tested by including a product term in the model 3 in the stratified analysis. We measured the interaction of the product term 26,27 . To further assess the robustness of results, we did the sensitivity analysis 1: we used continuous mode of these variables including age, mpox‐related knowledge and sexual diseases scores in model 3.…”
Section: Methodsmentioning
confidence: 99%
“…We measured the interaction of the product term. 26 , 27 All analyses were conducted using R 4.2.0. A two-sided P value less than .05 was considered to be statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…A study in the UK has shown that frailty was associated with mortality from respiratory diseases, while healthy behavior was able to mediate frailty to a certain extent. Therefore, promotion of a healthy lifestyle may be able to substantially attenuate the contribution of frailty to mortality from respiratory diseases (72).…”
Section: Chronic Disease Management and Frailtymentioning
confidence: 99%